Assessment of the variability of atmospheric pollution in National Parks of mainland Spain. (May 2016) - Escudero, M.; Lozano, A.; Hierro, J.; Tapia, O.; del Valle, J.; Alastuey, A.; Moreno, T.; Anzano, J.; Querol, Xavier
Abstract: Air quality in nine National Parks in mainland Spain was assessed analysing SO 2, NO x, O 3, PM 10 and PM 2.5 data from background stations. As emissions in and around parks are limited, the levels of primary pollutants are low. Concentrations of secondary pollutants are high especially in summer due to photochemical production. The geographical variability of pollutants responds to regional emission patterns and the dominant circulation regimes in different regions resulting in west-east gradients for O 3 and PM . Seasonal variability of pollutants was also interpreted in virtue of transport scenarios, changes in photochemical activity and emissions variability. NO x and SO 2, maximize in winter due to higher emissions while O 3 and PM do it in summer due to photochemical production, lower precipitation and, in the case of PM, the occurrence of African dust outbreaks. The diurnal evolution was interpreted in virtue of variability in emissions and changes in the Planetary Boundar Layer height. Highlights: First comprehensive assessment of the levels of atmospheric pollutants in National Parks in Spain. Regional sources and the influence of transport scenarios affect pollutants levels in National Parks. Emissions patterns and changes in the PBL height explain seasonal variability of pollutants. Ozone exhibit high levels in National Parks increasing concentrations towards the east of Iberia. Analysis of daily variability reveal impact of anthropogenic sources in some parks.